5x-8x+3x-6x=

Simple and best practice solution for 5x-8x+3x-6x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-8x+3x-6x= equation:


Simplifying
5x + -8x + 3x + -6x = 0

Combine like terms: 5x + -8x = -3x
-3x + 3x + -6x = 0

Combine like terms: -3x + 3x = 0
0 + -6x = 0
-6x = 0

Solving
-6x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-6'.
x = 0

Simplifying
x = 0

See similar equations:

| 11-8x=134-29x | | x-(x*0.10)=83 | | .222222222s=-6 | | (n-2)(n-1)=0 | | 3x^2-2x=81-2x-x^2 | | 5x+6=-99+10x | | (2r+1)(r-5)=0 | | 2=5x+1 | | 2x+28=10x-52 | | 5x+10=95+x | | (m-5)(3m+1)=0 | | 8-x=29 | | -3+5=5a | | 10(x-5)+25=10x-5(10-x) | | z^2+9=0 | | (2v-2)=0 | | 12a^2=-3 | | 4x^2=-3x | | [4-y]=1 | | 13=-3+2a | | 8+3x=x-2 | | 3x+13-73=3x | | 3x+30=15x-60 | | -1=-1+x | | -0.166t=9 | | 6d+5=3d+23 | | 3x(4+5)=4 | | 5.68+.81= | | 0.05=0.2x-10 | | 16(x-278)=6(x-8) | | -9=-2+2x | | -.75x=-4 |

Equations solver categories